PENGARUH PENGGUNAAN LAHAN TERHADAP KUALITAS AIR TANAH DI KOTA PAYAKUMBUH - Siti Nur Azmi; Sari Nova (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to identify the influence of land use on groundwater quality in Payakumbuh City. A quantitative approach was employed using secondary data from 30 well points located in Payakumbuh City and several areas in Lima Puluh Kota Regency. The analytical methods used include descriptive analysis, spatial analysis, and non-parametric statistical analysis. The results indicate that land use in 2024 does not have a statistically significant effect on groundwater quality based on the Kruskal-Wallis test, except for the Dissolved Oxygen (DO) parameter, which shows a significant influence with an H value of 7.85. Other parameters, such as pH (H = 3.38), Electrical Conductivity (DHL) (H = 3.04), and turbidity (H = 0.003), do not exhibit significant differences. Descriptively, residential areas show a tendency toward decreased groundwater quality compared to other land use types. Therefore, it can be concluded that certain land uses, such as residential areas, may influence groundwater quality, particularly in relation to dissolved oxygen levels (DO).